Ergovaline concentrations in simulated herbivory experiment - Tanentzap, Andrew J.; Vicari, Mark; Bazely, Dawn R. (Dryad Digital Repository, 2014)
Data are from an experiment simulating herbivory and saliva application on 32 Festuca rubra plants infected with Epichloë festucae. We used two simulated herbivory treatments consisting of fortnightly and monthly clipping and a control of no herbivory. Clipped plants received either distilled water or moose saliva. The 32 plants represented 22 isolates (putatively different genets), originating from either the core of F. rubra’s distribution in Europe, mainly Sweden, or its natural southern limit in southern Ontario, Canada. Plants were harvested after growing in a greenhouse for eight weeks and measured for ergovaline concentrations using high-performance liquid chromatography at the Endophyte Service Laboratory, Oregon State University.